On the Origins of Global History - Sanjay Subrahmanyam (Collège de France, 2016)
How does one think of history on a world scale? Should one turn to the intellectuals of the past or the historians of the present? Universal history as it was practised from Antiquity started to change from the sixteenth century in varied contexts, from East Asia to Spanish America. Applying his extensive knowledge of archives across the world and his command of languages and historiographic traditions of Asia, Europe and the Americas, Sanjay Subrahmanyam considers the history of networks and...